2007
DOI: 10.1111/j.1478-3231.2007.01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal core promoter T1762/A1764 and precore A1896 gene mutations in hepatitis B surface antigen‐positive hepatocellular carcinoma: a comparison with chronic carriers

Abstract: Background: Chronic hepatitis B virus (HBV) infection is associated with hepatocellular carcinoma (HCC), and specific viral factors have been identified that may increase the risk for HCC development. However, the differences in these viral factors in chronic carriers who seldom develop HCC compared with HCC patients have not been adequately evaluated. Methods: From 1989 to 2005, 101 hepatitis B surface antigen-positive patients presented to our clinic with HCC. Baseline basal core promoter (BCP) T1762/A1764 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 38 publications
9
78
2
6
Order By: Relevance
“…For instance, a Taiwanese study showed that the presence of the PC mutation significantly increased the risk for HCC [9], while another community-based cohort study with long-term follow-up conducted in the same country demonstrated that this mutant was associated with a decreased risk of HCC development [24]. In this study, our data showed that this common variant might not account for the increased risk of HCC among Thai populations.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…For instance, a Taiwanese study showed that the presence of the PC mutation significantly increased the risk for HCC [9], while another community-based cohort study with long-term follow-up conducted in the same country demonstrated that this mutant was associated with a decreased risk of HCC development [24]. In this study, our data showed that this common variant might not account for the increased risk of HCC among Thai populations.…”
Section: Discussioncontrasting
confidence: 49%
“…The other common HBV variants include double mutations in the basal core promotor (BCP) region (A1762T/ G1764A), which overlap with the ORF of the X gene and result in substantial decreases in HBeAg production [5]. These dual mutants have been reported in up to 50-80% of patients with HBeAg-negative chronic hepatitis B in Europe and Asia [6], and have been implicated in HCC development [7][8][9]. Apart from these variants, other mutations, such as T1753C/A/G in the BCP region and C1653T in the enhancer II region (EnhII) have become increasingly recognized as being associated with the outcome of chronic HBV infection, including HCC development [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…11,30 Other studies have shown that basal core promoters T1762/ A1764 mutants were more frequently detected in HCC patients and in patients with decompensated liver disease. 31-,34 The role of precore A1896 mutants is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Mutasi pada daerah precore ini sering ditemukan pada penderita hepatitis B kronik dengan HBeAg negatif dan telah dilaporkan berhubungan dengan terjadinya KH pada penderita hepatitis B kronik. 18 Untuk memperoleh informasi lebih lanjut tentang pengaruh varian VHB pada perjalanan penyakit hepatitis B kronik perlu dilakukan penentuan frekuensi mutasi ini pada berbagai genotipe VHB. Sebagai informasi awal, penelitian yang dilakukan oleh peneliti pada tahun 2006 didapatkan mutan precore pada 93% penderita hepatitis B kronik aktif dan 73% donor darah.…”
Section: Pembahasanunclassified